The influence of verbal encouragement on corporal stability during the traditional frontal plank exercise in young health adults: a pilot study - Costella, Taís; Tamiris Beppler Martins; Állan Goulart Medina; Mayane dos Santos Amorim Botti; Patrícia Parizotto; Maria Elisa Duarte França; Gilmar Moraes Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: It’s known that the frontal plank exercise presents a greater demand of the biomechanics stability and it is largely prescribed and used during the practice by the health professionals, known the verbal encouragement influence on corporal stability through the professional feedback can contribute positively in the clinical, social and scientific field. Objectives: Verify the verbal encouragement influences on corporal stability during the traditional frontal plank exercise in young health adults. Methods: Subjects were selected in an intentional non-probabilistic way, constituting a sample of young male adults, with normal body mass index, moderate to advanced self-reported physical activity level and with, at least, six months of previous resistance training experience. Participants were instructed to perform the traditional frontal plank for 30 seconds keeping all the items in the description of the technique, no command was given besides the following verbal incentives: “Contract, stabilize, force, maintain and force”. After the execution, the professional self-reported his perception of body stability, writing down his answers on the control form. Results: The sample consisted of 10 participants, with a mean age of 30.6 years (±4.03). All male, white and with no history of trauma/injury. For individuals with less than one time of weekly physical exercise, verbal encouragement showed a positive response in the perception of body stability. As for the remainder, who practiced physical exercise with greater recurrence, the evaluator’s perception of high stability was given both with and without verbal encouragement. Conclusion: This pilot study showed that in individuals with less time of weekly physical exercise, verbal encouragement showed a positive response in body stability, changing from moderate to high. But, the individuals with more time of practice, the verbal encouragement showed no response in the perception of body stability.